The Role of Government Subsidies in Promoting Green Investments in Renewable Energy Projects in Indonesia - Nisrina Jinan; Manna Salman Mahmud (Generasi Sains Indonesia, 2025)
This study investigates the role of government subsidies in promoting green investments in Indonesia’s renewable energy sector. With the goal of achieving a 23 percent renewable energy mix by 2025, Indonesia has implemented various fiscal policies, including subsidies, tax incentives, and feed-in tariffs to encourage investment in green energy. A qualitative methodology was adopted, relying on secondary data analysis from government reports and international institutions. The findings indicate that while subsidies have encouraged investment in renewable energy, their effectiveness is limited by the ongoing reliance on fossil fuel subsidies and institutional barriers such as fragmented governance and regulatory uncertainty. The study suggests that shifting fiscal support from fossil fuels to renewable energy, implementing performance-based subsidy programs, and improving governance structures could significantly enhance the effectiveness of subsidies. The main contribution of this research is its comprehensive assessment of Indonesia’s subsidy landscape and its implications for the country's energy transition. This study highlights the need for coordinated, long-term policy strategies to align fiscal policies with sustainability goals and suggests avenues for future research, including evaluating the socio-economic impacts of subsidy reforms.